Erythrocyte Shrinkage and Cell Membrane Scrambling after Exposure to the Ionophore Nonactin. Issue 2 (11th September 2015) - Peter, Thomas; Bissinger, Rosi; Lang, Florian
Abstract: The ionophore antibiotic nonactin permeabilizes cell membranes to NH 4 + and K + . Treatment of erythrocytes with nonactin is expected to trigger cellular K + loss with subsequent cell shrinkage, which in turn is known to trigger suicidal death of a wide variety of cells including erythrocytes. This study explored whether nonactin exposure induces eryptosis, the suicidal erythrocyte death characterized by cell shrinkage and translocation of cell membrane phosphatidylserine to the erythrocyte surface. Signalling of eryptosis includes increase in cytosolic Ca 2+ activity [(Ca 2+ )i ] and stimulation of protein kinase C (PKC) as well as p38 mitogen‐activated protein kinase. Phosphatidylserine abundance at the cell surface was estimated from annexin‐V‐binding, cell volume from forward scatter (FSC) and (Ca 2+ )i from Fluo3‐fluorescence. A 48‐hr treatment of human erythrocytes with nonactin significantly decreased FSC (≥10 ng/ml) and significantly increased the percentage of annexin‐V‐binding cells (≥10 ng/ml), effects paralleled by increase in (Ca 2+ )i (≥50 ng/ml) and virtually abrogated by increase in extracellular K + concentration to 120 mM at the expense of Na + . The up‐regulation of annexin‐V‐binding after nonactin treatment was significantly blunted but not abolished by the removal of extracellular Ca 2+ and by addition of either PKC inhibitor staurosporine (0.4 μM) or p38 kinase inhibitor SB203580 (2 μM). In conclusion, exposure of erythrocytes to the K + ionophore nonactin induces erythrocyte shrinkage and subsequent erythrocyte membrane scrambling, effects involving cellular K + loss, Ca 2+ entry and activation of staurosporine as well as SB203580‐sensitive kinases.